2008
DOI: 10.1890/07-1881.1
|View full text |Cite
|
Sign up to set email alerts
|

Trait‐mediated Effects on Flowers: Artificial Spiders Deceive Pollinators and Decrease Plant Fitness

Abstract: Although predators can affect foraging behaviors of floral visitors, rarely is it known if these top-down effects of predators may cascade to plant fitness through trait-mediated interactions. In this study we manipulated artificial crab spiders on flowers of Rubus rosifolius to test the effects of predation risk on flower-visiting insects and strength of trait-mediated indirect effects to plant fitness. In addition, we tested which predator traits (e.g., forelimbs, abdomen) are recognized and avoided by polli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
115
2
9

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(127 citation statements)
references
References 19 publications
1
115
2
9
Order By: Relevance
“…We can therefore conclude that they are just avoiding flowers harbouring spiders (e.g. as in Gonçalves-Souza et al 2008). By contrast, bees encountering cryptic spiders started to avoid safe yellow flowers towards the end of the training phase ( figure 2c).…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…We can therefore conclude that they are just avoiding flowers harbouring spiders (e.g. as in Gonçalves-Souza et al 2008). By contrast, bees encountering cryptic spiders started to avoid safe yellow flowers towards the end of the training phase ( figure 2c).…”
Section: Discussionmentioning
confidence: 87%
“…Gonçalves-Souza et al 2008), but can extend to an entire population of flowers with similar appearance (typically of the same species). In particular, we found that even though bumblebees are able to accurately detect and avoid cryptic spiders ( Ings & Chittka 2008), they chose to avoid all flowers resembling those that harboured cryptic spiders when alternative safe flower species were available.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, there is a lack of knowledge about the role of the chromatic and achromatic crypsis in the prey capture rate and survival rate against birds. Indeed, despite the growing number of studies using crab spider-prey interactions, there is not yet any evidence, for any prey, that decreasing chromatic and/or achromatic contrasts provides the spider with a benefit in terms of predation efficiency (Gonçalves-Souza et al, 2008;Yokoi and Fujisaki, 2009;Brechbühl et al, 2010a; Brechbühl et al, 2010b). These studies, however, revealed that the way prey behave in response to a crab spider is not only species specific but also individual specific.…”
Section: Are M Vatia Under Selection By Prey For Crypsis?mentioning
confidence: 99%